Unravelling the Shuttling Mechanism in a Photoswitchable Multicomponent Bistable Rotaxane - Raiteri, Paolo; Bussi, G.; Cucinotta, C.; Credi, A.; Stoddart, J.; Parrinello, M. (Wiley-VCH Verlag GMBH, 2008)
On the move: A computational investigation of the photo-triggered shuttling of a multicomponent bistable rotaxane in solution has shown that decomplexation of the counterions from the positively charged stations may be the efficiency-limiting step of the nanomachine. The picture shows the free-energy profile as a function of the ring position for the oxidized (ground) state (blue) and the reduced state (red) generated by photoexcitation.